Gramsci, Politics, and Philosophy: A Composite Theory of Ideology - Bernstein, Aaron (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
Although in comparison to other key Gramscian concepts, ideology has not been among the most studied, this is beginning to change. In particular, recent scholarship has demonstrated a diffuse and variegated usage of the term in the Prison Notebooks, as well as an innovative extension of the concept, which is articulated around a network of closely correlated terms and concepts. Nevertheless, debates remain over how to understand its meaning in Gramsci’s carceral discourse, with some arguing that his distinctive conception of ideology has a “neutral”, and arguably, also “positive” meaning, while others contend that it is neither “neutral”, nor “positive”, but a critical concept. This essay argues that Gramsci’s conception of ideology is neither neutral nor positive, but rather, an eminently critical and differentiated analysis of the diverse ideological forms of consciousness through which the popular masses are enveloped within the web of a class’s hegemony through the mediation of the philosophers’ philosophies, the fruit of his attempt to rethink philosophy politically. In short, understanding Gramsci’s conception of ideology in the full sense can only be ascertained by following the threads of his philosophical investigations in their shifts and re-elaborations. Keywords: Gramsci, Politics, Philosophy, Ideology